Accelerometry-based monitoring of daily physical activity in children with juvenile idiopathic arthritis. (3rd May 2016) - Nørgaard, M; Twilt, M; Andersen, LB; Herlin, T
Abstract : Objectives : Juvenile idiopathic arthritis (JIA) may cause functional impairment, reduced participation in physical activity (PA) and, over time, physical deconditioning. The aim of this study was to objectively monitor daily free-living PA in 10–16–year-old children with JIA using accelerometry with regard to disease activity and physical variables and to compare the data with those from healthy age- and gender-matched controls. Method : Patients underwent an evaluation of disease activity, functional ability, physical capacity, and pain. Accelerometer monitoring was assessed using the GT1M ActiGraph. Normative data from two major studies on PA in Danish schoolchildren were used for comparison. Results : Data of accelerometry were available for 61 JIA patients and 2055 healthy controls. Of the JIA patients, 57% showed below-average values of maximal physical capacity (fitness level). JIA patients showed low disease activity and pain and were physically well functioning. Accelerometer counts were lower in JIA patients than in controls. Accelerometer measurements were negatively correlated with disease activity, erythrocyte sedimentation rate (ESR), and number of joints with swelling and/or limited range of motion (ROM). No correlation was found between PA and pain scores, functional ability, and hypermobility. Patients with involvement of ankles or hips demonstrated significantly lower levels of PA. Conclusions : Children with JIA are less physically active and have lower physical capacity and fitness than their age- and gender-matched healthy peers despite good disease control. The involvement of hips or ankles is associated with lower PA.